2014
DOI: 10.1136/archdischild-2014-306961
|View full text |Cite
|
Sign up to set email alerts
|

Infant suffocation in place of sleep: New Zealand national data 2002–2009

Abstract: Accidental suffocation in bed was responsible for 48 preventable deaths. Prevention of these accidental deaths needs to focus on supporting changes in family behaviour with safety messages that are consistent, persistent and disseminated widely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…The risks for infants of cosleeping with a parent influenced by alcohol or drugs are well recognised, the most recent case–control study of SUDI determined an OR of 10.34 for infants cosleeping with parents who had consumed more than 2 units of alcohol or used illicit drugs when compared with similarly high-risk socially deprived controls 14. A review of national child mortality in New Zealand found that one-quarter of SUDI occurred away from home with infants sleeping in makeshift beds15; this is similar to our results where unplanned changed in family circumstances and living arrangements immediately preceded deaths in one-third of cases. Although none of the deaths were classified as due to accidental asphyxia, the circumstances of death would suggest that asphyxia was highly probable in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…The risks for infants of cosleeping with a parent influenced by alcohol or drugs are well recognised, the most recent case–control study of SUDI determined an OR of 10.34 for infants cosleeping with parents who had consumed more than 2 units of alcohol or used illicit drugs when compared with similarly high-risk socially deprived controls 14. A review of national child mortality in New Zealand found that one-quarter of SUDI occurred away from home with infants sleeping in makeshift beds15; this is similar to our results where unplanned changed in family circumstances and living arrangements immediately preceded deaths in one-third of cases. Although none of the deaths were classified as due to accidental asphyxia, the circumstances of death would suggest that asphyxia was highly probable in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects standard UK practice as in 2014 only 6 infant deaths nationally were registered with ICD10 code W75 (accidental suffocation and strangulation in bed) [19].There is a wide variation internationally in the use of ICD10 code W75 for infant sleep related deaths, ranging from 1.1% in Germany to 31.7% in New Zealand with England and Wales at 3.8% [20]; some of this variation may be due to differences in CDR with countries such as New Zealand having a robust CDR process [21]. Additionally, in our study only around half of unexplained deaths were categorised as SIDS with the remainder, especially those with more risk factors, labelled as undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Infants exposed to maternal cigarette smoking in the antenatal period have impaired arousal . A bed‐sharing environment provides a situation of multiple potential hazards for accidental asphyxia and hypoxia, especially for infants less physiologically capable of arousing and appropriately responding . Intervening in the substantial SUDI risk created by the interaction of bed‐sharing when there has been smoking in pregnancy provides the best opportunity to substantially impact SUDI rates …”
mentioning
confidence: 99%